SEROPREVALENCE OF HEPATITIS B AND C IN YOUNG ADULTS SEEKING RECRUITMENT IN ARMED FORCES - Mirza, Irfan Ali; Mirza, Sajjad Hussain; Irfan, Sabahat; Siddiqi, Rashad; Tariq, Waheed Uz Zaman; JANJUA, ASIF NAWAZ (Pakistan Armed Forces Medical Journal, 2006)
Background: Hepatitis B virus (HBV) and hepatitis C virus (HCV) are the commonest causes of chronic liver disease all over the world including Pakistan. According to the Pakistan Armed Forces policy, all the military recruits are now screened for the Hepatitis B surface antigen (HBsAg) and antibodies to Hepatitis C virus (Anti-HCV) before induction. Previous studies have shown a wide variation in the results regarding the prevalence of HBV and HCV infections. We analysed sera of 15550 young adults seeking recruitment in Armed forces for the presence of HBsAg and Anti-HCV.Materials and Methods: Sera of healthy adult individuals who presented for medical evaluation as prerecruitment criteria in the Punjab Regiment Centre, Mardan, were tested for presence of hepatitis B surface antigen (HBsAg) and anti-hepatitis C virus (Anti-HCV) by rapid method. Positive cases were confirmed by ELISA technique from Armed Forces Institute of Pathology (AFIP) Rawalpindi.Results: A total of 15550 individuals were examined. Out of these, 504 (3.24%) individuals had positive HBsAg whereas 574 (3.69%) were positive for anti-HCV. Hepatitis B surface antigen and anti-HCV both were found in 49 (0.31%) individuals.Conclusion: This study which evaluated predominantly healthy young male population, showed a high seroprevalence of anti-HCV than Hepatitis B surface antigen. Although there is downward trend in prevalence of hepatitis B, there is considerable threat of HBV and HCV to our younger population and there is a genuine need for strict adherence to preventive measures.